The Implementation of Research Based Learning Materials on Student Learning Competency in Islamic Higher Institution - Tenny Sudjatnika (Jurnal Pendidikan Islam, 2021)
The study on research-based learning material needs to be introduced in universities in order to achieve student competence. The purpose of this study is to investigate the contribution of teaching materials for Islamic Studies courses to be internalized in order to achieve the competence of English literature study program. This research applied qualitative method using an action research approach. Data were collected using tests, observations and interviews. The data were analyzed in the form of student learning performance. Their performance included students' thinking styles, patterns of processing information, attitudes and their work. Based on Thorndike's theory of connectionism, it was found that the draft teaching materials implemented through the classroom learning process in the form of thinking styles and ways of processing information were in accordance with their competencies. The implementation of the learning process was carried out through the internalization of Islamic educational values which can be seen in the attitude of students' politeness and the work they obtained.